Accessory cervical thymus presenting in conjunction with a thyroglossal duct cyst. Issue 1 (January 2015) - Boerner, Ryan; Bigcas, Jo-Lawrence; Christensen, Paul; Roy, Soham
Abstract: We present an unusual case of a lateral neck mass presenting in conjunction with a thyroglossal duct cyst with review of literature. A 7-year-old boy presented with a midline mass consistent with a thyroglossal duct cyst and a second lesion adjacent to the left inferior lobe of the thyroid confirmed to be ectopic thymus after excision. This is the first reported case of ectopic cervical thymus diagnosed in conjunction with a thyroglossal duct cyst. It is possible that both lesions developed by a similar mechanism. The treatment of choice for both masses is surgical excision.